Enteric Microbiome Markers as Early Predictors of Clinical Outcome in Allogeneic Hematopoietic Stem Cell Transplant: Results of a Prospective Study in Adult Patients. (6th October 2017) - Mancini, Nicasio; Greco, Raffaella; Pasciuta, Renée; Barbanti, Maria Chiara; Pini, Giacomo; Morrow, Olivia Beatrice; Morelli, Mara; Vago, Luca; Clementi, Nicola; Giglio, Fabio; Lupo Stanghellini, Maria Teresa; Forcina, Alessandra; et al.
Abstract: Background: Infections and graft-vs-host disease (GvHD) still represent major, not easily predictable complications in allogeneic hematopoietic stem cell transplant (allo-HSCT). Both conditions have been correlated to altered enteric microbiome profiles during the peritransplant period. The main objective of this study was to identify possible early microbiome-based markers useful in pretransplant risk stratification. Methods: Stool samples were collected from 96 consecutive patients at the beginning of the pretransplant conditioning regimen (T0 ) and at 10 (T1 ) and 30 (T2 ) days following transplant. When significant in univariate analysis, the identified microbiome markers were used in multivariate regression analyses, together with other significant clinical variables for allo-HSCT-related risk stratification. Four main outcomes were addressed: (1) septic complications, (2) GvHD, (3) relapse of the underlying disease, and (4) mortality. Results: The presence of >5% proinflammatory Enterobacteriaceae at T0 was the only significant marker for the risk of microbiologically confirmed sepsis. Moreover, ≤10% Lachnospiraceae at T0 was the only significant factor for increased risk of overall mortality, including death from both infectious and noninfectious causes. Finally, a low bacterial alpha-diversity (Shannon index ≤ 1.3) at T1 was the only variable significantly correlating with an increased risk of GvHD within 30 days. Conclusions: Microbiome markers can be useful in the very early identification of patients at risk for major transplant-related complications, offering new tools for individualized preemptive or therapeutic strategies to improve allo-HSCT outcomes.